Empowerment of Micro, Small and Medium Enterprises Based on Upland Rice through Strengthening Legality and Digital Promotion in Sekurau Atas Village, Bengalon, East Kutai, East Kalimantan: Pemberdayaan Usaha Mikro, Kecil dan Menengah Berbasis Produk Lokal Masyarakat Desa Sekurau Atas di Bengalon, Kutai Timur, Kalimantan Timur - Paramita, Swandari; Serliana, Selvi; Naibaho, Rima Christine Natalie; Syaidhina, Rachel Syafa; Patrisia, Putri; Sardjitha, Ni Made Karmini Belva; Rongre, Jumiati; Al-Qadhri, Farhan Mustaqim; Zalianti, Alya Aditia; Wahitdah, Nur; Nugraha, Prayoga Adhi; Manalu, Shary Uly Actaviany (B-Creta Publisher, 2025)
Sekurau Atas Village in Bengalon, East Kutai, East Kalimantan, has natural resource potential that can be developed into a local superior product, namely padi gunung (upland rice). However, Micro, Small, and Medium Enterprises (MSMEs) in Sekurau Atas Village still face limitations in business management, product innovation, and marketing. This community service program aims to empower MSMEs based on local village products, particularly padi gunung. The methods implemented include socialization of the economic potential of padi gunung, packaging development for padi gunung products, education on obtaining a Business Identification Number (NIB), Home Industry Food Production Permit (PIRT), and halal certification for padi gunung products, as well as the creation of social media advertisements and infographics for padi gunung. The results showed an increase in MSME stakeholders’ knowledge in business management, improved product quality, and expanded market access through social media. This program is expected to enhance the community’s economic independence and promote the sustainability of MSMEs based on local potential. In addition, this empowerment model can be replicated for the development of other local superior commodities, supporting sustainable village economic development.